3D Pen Tactile Pictures Generated by Individuals with Visual Impairments. (September 2020) - Wu, Chih-Fu; Wu, Hsiang-Ping; Tu, Yung-Hsiang; Yeh, I-Ting
Introduction: Individuals with visual impairments acquire information about objects through touch and by use of auxiliary tactile pictures. The current study introduced a new three-dimensional (3D) printing pen technology as a research tool to allow individuals with visual impairments to convert tactile experiences to convex tactile pictures. Methods: Participants with visual impairments used a 3D pen to draw pictures of daily necessities. The actions and time related to the entire drawing activity were recorded on video. Results: We noted three behaviors during the use of 3D pen: drawing, touching the trace lines, and finding location points. The object-depiction angle, component-completeness description, and drawing-line presentation differed between subjects with congenital and those with acquired blindness. Discussion: Individuals with congenital blindness depicted objects mainly from an operational angle, and those with acquired blindness from the angle of the object when laid flat. When the components of an object were relatively complex, the subjects with congenital blindness only drew local features in contact with their bodies and with continuous line segments, and those with acquired blindness used discontinuous line segments. Participants were satisfied that the 3D printing pen could touch the drawing path in time and that they could use the "piling" feature to create positioning marks or planar expressions. Implications for practitioners: Students can be instructed to use 3D pens to draw (lines, planes, and objects) to enhance the communication between teachers and students and improve teaching efficiency. Regarding the design of tactile pictures, the parts that come in contact with the body during object use can be considered the reference features of the pictures. For large pictures, attention should be paid to the size ratio between the outline and components. For small pictures, one should consider how the operational feature details should be shown at approximately the original size.